Successes in Reducing Cause-Specific Mortality, United States, 2000-2019 - George Rust; Tyra Dark; Ransome Eke; Robert S. Levine; Jeffrey Harman (Public Health Reports®, 2026)
Objective: Major successes in improving health in the United States during the past century have occurred as our nation moved through the epidemiologic transition from high infectious disease mortality to predominantly chronic disease mortality. The objective of this study was to identify successes in improving America’s health in the first 2 decades of the 21st century. Methods: We identified leading causes of death among US adults with age-adjusted mortality rates that declined by ≥20% from 2000 to 2019. Results: Eleven disease categories achieved a ≥20% mortality reduction, including the leading causes of death in the United States (heart disease, stroke, cancer) and 2 infectious diseases. Seven of the 11 “success” conditions were forms of cancer, showing progress in screening, early diagnosis, treatment, and cure. A cautionary note is warranted for conditions with increasing cause-specific mortality, such as brain diseases, suicide, drug overdose, accidental deaths, and liver disease. Conclusions: The impact of research innovation translated into prevention and medical care is clearer with each passing decade. Similar strategies that prioritize behavioral health will be needed to reverse conditions with worsening mortality. Successful public health strategies have continued to reduce mortality from somatic “below-the-neck” causes, but parallel strategies are needed to address mental health, substance use, health behaviors, and healthy aging.